Perceptions of doctors disclosing AI use in their online biographies: evidence from an experiment - Evan K. Perrault; Gladys M. Momade; Eylül Yel (International Journal of Pharmaceutical and Healthcare Marketing, 2026)
Purpose Health-care systems are continuing to integrate artificial intelligence (AI) into their workflows and promote its adoption. Therefore, the purpose of this study was to investigate how prospective patients feel about individual providers harnessing AI within their own practices. Design/methodology/approach This study experimentally exposed participants (n = 466) to online biographies of primary care physicians disclosing that the physician either consulted with AI, or physician colleagues, in their medical practices. Findings Doctors who indicated using AI were perceived as less expert, trustworthy and approachable. Participants also believed the AI-consulting doctor would provide a lower quality of care. A greater number of participants indicated less willingness to make a future appointment with an AI-consulting doctor. Originality/value Recommendations for health-care marketers considering incorporating providers’ disclosure of AI collaboration within their online biographies are discussed, as well as future directions for research.